Maternal obesity modulates intracellular lipid turnover in the human term placenta - Hirschmugl, B (Int J Obes (Lond), 2017)
BACKGROUND: Obesity before pregnancy is associated with impaired metabolic status of the mother and the offspring later in life. These adverse effects have been attributed to epigenetic changes in utero, but little is known about the role of placental metabolism and its contribution to fetal development. OBJECTIVES: We examined the impact of maternal pre-pregnancy obesity on the expression of genes involved in placental lipid metabolism in lean and obese women. SUBJECTS/METHODS: Seventy-three lean and obese women with healthy pregnancy were recruited at term elective cesarean delivery. Metabolic parameters were measured on maternal venous blood samples. Expression of 88 genes involved in lipid metabolism was measured in whole placenta tissue. Proteins of genes differently expressed in response to maternal obesity were quantified, correlated with maternal parameters and immunolocalized in placenta sections. Isolated primary trophoblasts were used for in vitro assays. RESULTS: Triglyceride (TG) content was increased in placental tissue of obese (1.10, CI 1.04–1.24 mg g(−1), P<0.05) vs lean (0.84, CI 0.72–1.02 mg g(−1)) women. Among target genes examined, six showed positive correlation (P<0.05) with maternal pre-pregnancy BMI, namely ATGL (PNPLA2), FATP1 (SLC27A1), FATP3 (SLC27A3), PLIN2, PPARG and CGI-58 (ABHD5). CGI-58 protein abundance was twofold higher (P<0.001) in placentas of obese vs lean women. CGI-58 protein levels correlated positively with maternal insulin levels and pre-pregnancy body mass index (R=0.63, P<0.001 and R=0.64, P<0.001, respectively). CGI-58 and PLIN2 were primarily located in the syncytiotrophoblast and, were upregulated (1.38- and 500-fold, respectively) upon oleic acid and insulin treatment of cultured trophoblast cells. CONCLUSION: Pre-gravid obesity significantly modifies the expression of placental genes related to transport and storage of neutral lipids. We propose that the upregulation of CGI-58, a master regulator of TG hydrolysis, contributes to the turnover of intracellular lipids in placenta of obese women, and is tightly regulated by metabolic factors of the mother.